A study of the clinical, ultrasonographic, and bacteriological characteristics of abscesses in farm animals - Abdelhakiem, Mohammed A.H.; Malek, Safaa S.; Mokhtar, Aml (Journal of Advanced Veterinary Research, 2024)
Abscess is considered one of the most common surgical body surface swellings in farm animals. The recognition of the clinical, ultrasonographic and biochemical characters of abscesses is important in the management and control of this devastating swelling. One hundred twenty-two animals were selected out of two hundred and five animals presented abscesses in different body regions. The clinical and ultrasonographic examinations were carried out to verify the abscess development. The swabs and pus samples for bacteriological study were obtained before the surgical treatment once the abscess maturation was ascertained. The animals were normal clinically and there were no changes in the physiological parameters. The cattle represented the high percentage in abscess development (73.77%). The gluteal, umbilical and the subconjunctival regions were the common seats for abscess development. The size of abscesses varied from small orange to volleyball. In more than 90% of cases, the abscess was developed as a single lesion. The ultrasonographic examination showed that a well-demarcated echogenic wall for all abscesses, but its contents varied in echogenicity and homogeneity according to the type of abscess (acute or chronic) and its seat. Biochemically, a total two-hundred and ninety-two isolates were obtained which included eighteen single isolates and two-hundred and seventy-four mixed isolates. They included Corynebacterium and E. coli (n=40), S. aureus (n=38), S. epidermidis (n=36), Proteus (n=30), St. pyogenes (n=28), Neisseria (n=20), Bacillus subtilis (n=14), Bacillus cereus (n=12), Alcaligenes faecalis (n=12), Enterobacter aerogenes (n=10), Enterobacter aerogenes (n=6) and Klebsiella pneumonia (n=6). It could be concluded that there are multiple different species of micro-organisms could cause abscess formation in farm animals, and there is no specific micro-organism could be expected to be isolated from the abscess. Additionally, multiple different species of organisms could be isolated from the same abscess.